The effect of serum magnesium, calcium, and potassium levels on the event of calf muscle cramps, according to the perspective of pregnant women in the third-trimester of pregnancy : Pengaruh Kadar Magnesium, Kalsium, dan Kalium Serum Terhadap Terjadinya Kram Otot Betis, Menurut Perspektif Ibu Hamil di Trimester Ketiga Kehamilan - Cut N. Maracilu; Cut M. Yeni; Hasanuddin Hasanuddin; Hilwah Nora; Sarah I. Nainggolan (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objective: To determine the effect of magnesium, calcium, and potassium levels on calf muscle cramps in third-trimester pregnant women at Dr. Zainoel Abidin Banda Aceh. Methods: This research is an observational analytic study with a case-control method by taking samples using a total sampling technique. The research sample was third-trimester pregnant women (28-40 weeks of gestation) who were treated in the maternity ward for the period September to December 2020. Results: A total of 263 samples were involved in this study where 105 patients (40%) were obese, 229 patients (87%) were housewives, 161 patients (61%) did not experience muscle cramps and samples had magnesium levels below normal as much as 82 people, calcium levels below normal as many as 127 people and potassium levels below normal as many as 2 people. The mean levels of magnesium, calcium, and potassium were 1.8 mg/dL, 8.69 mg/dL, and 4.25 mmol/L, respectively. The results of this study are magnesium levels affect muscle cramps in pregnant women (p-value=0.000), while calcium levels (p-value=0.373) and potassium (p-value=0.062) do not affect muscle cramps in pregnant women. Conclusion: There is a significant effect between magnesium levels on the incidence of calf muscle cramps in third-trimester pregnant women, while calcium and potassium levels do not affect them. Keywords: Muscle Cramps, Magnesium, Calcium, Potassium.